124k views
9 votes
Help me with this question, please

Help me with this question, please-example-1
User Fajarkoe
by
4.9k points

1 Answer

7 votes

Answer:

Part 1: [ -4 = -8 ]

Part 2: Inconsistent

Explanation:

Part 1

1. Move all terms that don't contain x to the right side:

3x - 6y+6y = -12+6y

= 3x = -12 + 6y

2. Isolate x:


(3x)/(3) = (-12+6y)/(3)

x = -4 + 2y

3. Substitute the new expression into the original:

-4 + 2y - 2y = -8

4. Simplify:

-4 + 0 = -8

[ -4 = -8 ]

Part 2

The two solutions are not equal in value, so, we can conclude that the system of equations has no solution, or is inconsistent.

hope this helps!

User Klaudia
by
5.2k points